Online monitoring of fatigue damage using ultrasonic methods - Loke, Jin Hao (Nanyang Technological University, 2023)
Fatigue damage induced in engineering applications are inevitable, as such without proper monitoring it could cause serious consequences as fatigue failure can occur without any warning signs. The use of traditional ultrasound Non-Destructive Testing methods are widely used and proven to be a very effective technique to various important applications in a wide field of engineering industry. However, when faced with nonlinear defects in a material, traditional technique may not be as effective in detecting as it may be acoustic transparent. Various studies have been made on improving monitoring fatigue damage and also non-linear ultrasound Non-Destructive Testing with higher harmonics and it has shown promising results in detecting non-linear defects especially with the 2nd harmonics. In this project, two experiments will be conducted to monitor fatigue damage induced on a sample. The first experiment will use traditional ultrasonic wave from two piezoelectric attached on the sample to generate and receive signals at various frequencies. Second experiment will use Non-linear method from the use of two non- colinear shear wave from a probe of 5MHz frequency. The two shear waves will intersect to produce a longitudinal wave which will be receive by a 10MHz probe.